Pengembangan LKS Berbasis Problem Based Learning Pada Materi Sistem Persamaan Linear Dua Varibel Di Kelas VIII - Rahma Dani Ilham; Fazri Zuzano; Listy Vermana (RANGE: Jurnal Pendidikan Matematika, 2024)
This research was motivated by students lacking enthusiasm and being less active in learning mathematics. One effort to overcome this problem is to develop problem based learning worksheets because they can help teachers in developing student centered learning which makes students active in learning. This type of research is development using the ADDIE development model which has 5 stages, namely analysis, design, development, implementation and evaluation. Product trials were carried out at SMP N 1 Kuantan Hilir. The research subjects were 10 students in class VIII.2. The research results showed that problem based learning worksheets were valid by two validators. Worksheets based on problem based learning were declared practical with a score of 63%. So that problem based learning worksheets are valid and practical. From the research, it is recommended that teachers use LKS based on problem based learning as teaching materials and several shortcomings during the research include: (1) in groups of students only a few people are looking for answers and apart from that they only see answers from their group friends (2) students tended to tell stories during learning (3) the researcher did not take all the subjects in the class (4) when filling in the practicality sheet the students were not honest.